Peningkatan Hasil Belajar Materi Satuan Waktu Melalui Penerapan Metode Make a Match - Nursanti Rajagukguk (Journal on Education, 2021)
This study aims to determine whether or not there is an increase in the learning outcomes of the Unit of Time material through the application of the make a match method to Class 3-A students of SD Negeri Kendangsari I/276 Surabaya and to find out how much the increase in the learning outcomes of the Unit of Time material through the application of the make a match method in Class 3-A students of SD Negeri Kendangsari I/276 Surabaya. The research was carried out with a two-cycle action implementation mechanism with two meetings in each cycle. The subjects of this study were students of class 3-A SD Negeri Kendangsari I/276 Surabaya, totaling 39 students. In the study, it was found that the percentage of student learning outcomes in the Time Unit material from before this learning model was applied which only had an average of 54.3 to 70.9 in the first cycle and 77.1 in the second cycle. Based on the results of data analysis and discussion, it can be concluded that there is an increase in the learning outcomes of the Time Unit material through the application of the make a match method to Class 3-A students of SD Negeri Kendangsari I/276 Surabaya. The increase in learning outcomes of the Time Unit material through the application of the make a match method in Class 3-A students of SD Negeri Kendangsari I/276 Surabaya is an average of 23%.